Administration of broadly neutralizing anti-HIV-1 antibodies at ART initiation maintains long-term CD8+ T cell immunity - Rosás-Umbert, Miriam; Gunst, Jesper D.; Pahus, Marie H.; Olesen, Rikke; Schleimann, Mariane; Denton, Paul W.; Ramos, Victor; Ward, Adam; Kinloch, Natalie N.; Copertino, Dennis C.; Escribà, Tuixent; Llano, Anuska; et al. (Nature communications, 2022)
In simian-human immunodeficiency virus (SHIV)-infected non-human primates, broadly neutralizing antibodies (bNAbs) against the virus appear to stimulate T cell immunity. To determine whether this phenomenon also occurs in humans we measured HIV-1-specific cellular immunity longitudinally in individuals with HIV-1 starting antiviral therapy (ART) with or without adjunctive bNAb 3BNC117 treatment. Using the activation-induced marker (AIM) assay and interferon-γ release, we observe that frequencies of Pol- and Gag-specific CD8 + T cells, as well as Gag-induced interferon-γ responses, are significantly higher among individuals that received adjunctive 3BNC117 compared to ART-alone at 3 and 12 months after starting ART. The observed changes in cellular immunity were directly correlated to pre-treatment 3BNC117-sensitivity. Notably, increased HIV-1-specific immunity is associated with partial or complete ART-free virologic control during treatment interruption for up to 4 years. Our findings suggest that bNAb treatment at the time of ART initiation maintains HIV-1-specific CD8 + T cell responses that are associated with ART-free virologic control. Broadly neutralising anti-HIV-1 antibody (bNAb) administration in nonhuman primates has been shown to stimulate adaptive T cell-specific immunity, with infection prevention observed. In this work, the authors longitudinally analyse HIV-1 specific cellular immunity in HIV-1- infected individuals starting ART with or without adjunctive bNAb treatment.